Missed opportunity: low uptake of VMMC among men attending the OPD of a public health facility offering free VMMC services in Uganda - Ruth Nyaiti Kiyai; David Livingstone Ejalu; Derrick Kimuli (BMC, 2023)
Abstract Background Studies in various countries including Uganda and Kenya have shown a much lower incidence of the human immunodeficiency virus (HIV) among men that underwent voluntary medical male circumcision (VMMC) compared to uncircumcised men. Wakiso district, the district with the highest prevalence of HIV in Uganda (7%), has a very low estimated proportion of men who have undergone VMMC (30.5%). Within the district, various public health facilities provide free VMMC services. This study examined the prevalence and factors associated with the uptake of VMMC among men attending the outpatient department (OPD) of a public facility offering VMMC services. Methods We conducted a cross-sectional study between July to August 2021 using a sample of men attending the OPD at Kira Health Centre IV. We defined VMMC uptake as the removal of all or part of the foreskin of the penis by a trained healthcare professional. We determined factors independently associated with VMMC uptake using a modified Poisson regression analysis with robust standard errors at a 5% statistical significance level. Adjusted prevalence risk ratios (APRR) were reported as the measure of outcome. Results Overall, 389 participants were enrolled in the study. The mean age of the participants was 27.2 (standard deviation ± 9.02) years. The prevalence of VMMC uptake was 31.4% (95% Confidence Interval [CI] 26.8-36.2). In the adjusted analysis, the uptake of VMMC among men attending the OPD of Kira HC IV was less likely among married participants compared to unmarried participants (APRR 0.64, 95% CI 0.48-0.88), among participants from Western tribes (APRR 0.50, 95% CI 0.41-0.86) or Eastern tribes (APPR 0.31, 95% CI 0.13-0.72) compared to participants from the Central tribes and among participants who didn't disclose their sexual partner number compared to those that had one or no sexual partner (APRR 0.62, 95% CI 0.40-0.97). On the other hand, the prevalence of uptake of VMMC was 7 times among participants who were aware of VMMC compared to those who were not aware of VMMC (APRR 7.85 95% CI 1.07-9.80) and 2.7 times among participants who knew their HIV status compared to those that didn't know (APRR 2.75, 95% CI 1.85-4.0). Also, the uptake of VMMC was 85% more among participants who knew that Kira HC IV provided free VMMC services compared to those that didn't (APRR 1.85, 95% CI 1.85-4.08). Conclusion VMMC among men attending the OPD at the largest public healthcare facility proving free VMMC services in Kira Municipality was low. The OPD may provide a quick win for improving VMMC uptake. Collaborative efforts among the administration of Kira HC IV, the Ministry of Health and VMMC implementation partners could work towards developing health-facility-based strategies that can improve VMMC awareness and uptake with emphasis on the OPD.